Antecedents of symbolic adoption of Coretax as a mandatory tax system: The role of perceived usefulness - Leonardus Tandi Tola; Erna Fitri Komariyah; Yuni Putri Yustisi (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2026)
This research explores the factors influencing taxpayers' symbolic adoption of Coretax by combining the Technology Acceptance Model with supervisor influence within a compulsory digital taxation setting. Data gathered from 122 taxpayers and analyzed using PLS-SEM reveal how perceived ease of use, supervisor influence, and perceived usefulness affect symbolic acceptance. Results show that both perceived ease of use and supervisor influence significantly enhance perceived usefulness, which, in turn, positively affects symbolic adoption. Mediation analysis indicates that perceived usefulness fully mediates the relationships between perceived ease of use, supervisor influence, and symbolic adoption. The findings suggest taxpayers are more likely to adopt Coretax when they genuinely recognize clear practical benefits. Technical simplicity and managerial support alone are inadequate unless they lead to perceived utility. This study extends the TAM by incorporating symbolic acceptance as a key post-implementation outcome in a mandatory tax technology context. In practice, the results suggest that tax authorities should prioritize user-friendly system design, effective communication of system benefits, and strong supervisory support to foster genuine taxpayer acceptance and maximize the long-term success of digital tax transformation.